“Composição química e atividades biológicas das folhas de Podocarpus lambertii Klotzch ex Endl." - Bandeira, Debora Marina (2021)
Some essays in this study with the species Podocarpus lambertii are unprecedented because it is a Brazilian native plant traditionally used in reforestation, studies in relation to its biological potential are almost null when compared to other species of the genus. Thus, the aim of this study was to carry out phytochemical prospecting through colorimetric reactions, to determine the secondary metabolites present in plant extracts soluble in acetone (EAc), ethyl acetate (EAE), hexane (EHx), methanol (EM) ethanol (EE) and essential oil (EO). This study is the first to determine the phytochemical profile of essential oil (EO) and plant extracts from the leaves of Podocarpus lambertii, evaluate the antimicrobial activity by the broth microdilution technique, antioxidant activity by the 2,2-diphenyl-method method. 1-picryl hydrazyl (DPPH) and activity on preformed bacterial biofilms. The yield of EO was 0.36% and EM (14.9%), EE (9.76%), EAc (6.76%), EAE (7.60%) and EHx (4.51%) extracts . The chemical composition of the EO was determined by gas chromatography coupled with mass spectrometry (GC-MS) and identified 16 compounds, the major ones being: Manool, 13-epi- (30.30%), Rimuene (26.02%). The phytochemical exploration of the extracts revealed the presence of alkaloids, flavonoids, steroids, saponins and tannins. All extracts showed antimicrobial activity on the microorganisms tested (Escherichia coli, Salmonella enterica Enteritidis, Salmonella enterica Typhimurium, Salmonella enterica Abaetetuba, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae, Staphylococcus aureus, Enterococcus faecalis, Staphylococcus epidermidis, Bacillus subtillis, Candida albicans). Regarding antioxidant activity, EAc and EM extracts showed a high percentage of DPPH radical scavenging. The OE had low antimicrobial and antioxidant activity. High antibiofilm activity (<50%) of EM and a reduction in the biomass of the biofilm formed on most strains tested were observed. The results suggest that plant extracts of P. lambertii are a promising alternative source of natural bioactive compounds for the control of resistant microorganisms, in addition to contributing to the knowledge of the species.